Lipophilic Tetranuclear Ruthenium(II) Complexes as Two‐Photon Luminescent Tracking Non‐Viral Gene Vectors. Issue 9 (16th January 2015) - Yu, Bole; Ouyang, Cheng; Qiu, Kangqiang; Zhao, Jing; Ji, Liangnian; Chao, Hui
Abstract Fluorescence detection is the most effective tool for tracking gene delivery in living cells. To reduce photodamage and autofluorescence and to increase deep penetration into cells, choosing appropriate fluorophores that are capable of two‐photon activation under irradiation in the NIR or IR regions is an effective approach. In this work, we have developed six tetranuclear ruthenium(II) complexes, GV1–6, and have studied their one‐ and two‐photon luminescence properties. DNA interaction studies have demonstrated that GV2–6, bearing hydrophobic alkyl ether chains, show more efficient DNA condensing ability but lower DNA binding constants than GV1. However, the hydrophobic alkyl ether chains also enhance the DNA delivery ability of GV2–6 compared with that of GV1. More importantly, we have applied GV1–6 as non‐viral gene vectors for tracking DNA delivery in living cells by one‐ and two‐photon fluorescence microscopies. In two‐photon microscopy, a high signal‐to‐noise contrast was achieved by irradiation with an 830 nm laser. This is the first example of the use of transition‐metal complexes for two‐photon luminescent tracking of the cellular pathways of gene delivery and as DNA carriers. Our work provides new insights into improving real‐time tracking during gene delivery and transfection as well as important information for the design of multifunctional non‐viral vectors.